Characteristics and roles of streamers in e-commerce live streaming. Issue 13 (26th October 2022) - Zhang, Shengliang; Huang, Chaoying; Li, Xiaodong; Ren, Ai
ABSTRACT: Streamers are the individuals at the core of e-commerce live streaming (ELS), which is a successful influencer marketing strategy. However, a systematic profile of ELS streamers is lacking. This study aims to investigate the roles and characteristics of ELS streamers, as well as their matching relationships, by applying the grounded theory method to analyze semi-structured interviews of 96 consumers. Eight characteristics of ELS streamers (expertise, attractiveness, credibility, interactivity, popularity, price support, affinity, and responsiveness) are identified and further classified into four roles (opinion leader, spokesperson, interactive friend, and salesperson). This study is the first to create a role set for ELS streamers and the first to systematically elucidate the roles of ELS streamers and their corresponding characteristics. It not only supplements e-commerce, influencer marketing, and role theory research by identifying new characteristics and roles of ELS streamers, but it also provides a clear framework practitioners can use to train streamers.